Surgical and nonsurgical follow up results of ureteropelvic junction obstruction without diuretic response in pediatric patients - Koc, Z.; Gurgoze, M.; Bakal, U.; Balci, T. (Springer, 2013)
[Abstract Not Available]
Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 19-23, 2013 -- Lyon, FRANCE